A polymorphism in randomly amplified DNA that differentiates the Y chromosomes of Bos indicus and Bos taurus - Teale, A.J.; Wambugu, J.; Gwakisa, P.S.; Stranzinger, G.; Bradley, D.; Kemp, Stephen J. (Wiley, 1995)
A small number of west African Bos taurus cattle breeds, including the N'Dama, constitute a valuable genetic resource by virtue of their ability to remain productive under trypanosomiasis challenge. However, introgression of Bos indicus genes into the trypanotolerant breeds, particularly by introduction of zebu bulls, is a threat to this resource. This work describes the characterization and cloning of a bovine randomly amplified polymerase chain reaction (PCR) with the 10 base primer ILO1065 from Bos indicus male templates, but not from B. taurus male templates of female templates of either type. Male-specific sequences with homology to the RAPD also occur in B. taurus breeds. This suggests that the polymorphism may be due to base substitution(s) in an ILO1065 priming site, or insertion/deletion events either affecting priming sites or occurring between sites on the cattle Y chromosome. We have shown that cattle, whether of B. indicus or B. taurus phenotype, which possess a typically B. indicus metaphase Y chromosome on the basis of QFQ banding, have a B. indicus ILO1065-generated genotype. The ILO1065-primed RAPd can be used in a simple dot blot assay as a probe of RAPD-PCR products, to provide a convenient, reliable and effective means of detecting introgression of zebu genes in B. taurus cattle populations.